KAJIAN PROSES PRODUKSI KATALIS MIKROSFERIK UNTUK PERENGKAHAN MINYAK BUMI DENGAN PENGERING SEMBUR - AJI HENDRA SAROSA; Tjokorde Walmiki Samadhi; B Budiyanto (Dept. of Chemical Engineering, Diponegoro University, 2015)
STUDY OF SPRAY DRYING PROCESS FOR THE PRODUCTION OF PETROLEUM CRACKING CATALYST. Catalyst for the hydrocarbon fluid catalytic cracking (FCC) process consists of zeolite, matrix, fillers, and binders. The FCC catalyst has a microsphere form (10-120 µm), and can be produced by spray drying. Operating conditions of spray drying affect the characteristics of the microspheres FCC catalyst. The composition slurry (24% by weight) is 27% (by weight) of zeolite NaY, 33% (by weight) of Belitung kaolin, 20% (by weight) of silica alumina, 20% (by weight) of silica sol. The slurry is fed to spray dryer with constant air temperature of 190oC, ratio of atomizing air flow to slurry feed rate between 0.75:1 to 1:1, hot air flow rate between 0.2-0.3 m3/min, and slurry feed rate between 15-20 mL/min. Catalyst particle size distribution produced is in the range of 0.3752-161.1770 µm. Angle of repose of the dry product isin the 41.45-49.00 range, which translates to a flowability between passable and poor. Statistical treatment of experimental data by ANOVA method indicates that hot air velocity and interaction between the atomizing air to slurry feed rate ratio and the hot air velocity significantly affect the average particle size. The interaction between the atomizing air to slurry feed ratio with hot air velocity significantly affect particle size distribution as well. Keywords: FCC catalyst; operation conditions; spray drying Abstrak Katalis FCC memiliki empat komponen yaitu zeolit, matriks, bahan pengisi, dan bahan pengikat. Katalis FCC berbentuk mikrosfer berukuran 10-120 µm. Produksi katalis FCC melibatkan operasi pengering sembur. Kondisi operasi pengering sembur mempengaruhi karakteristik katalis FCC mikrosfer. Campuran slurry (24% berat) memiliki komposisi 27% (berat) zeolit NaY, 33% (berat) kaolin Belitung, 20% (berat) silika alumina, 20% (berat) silika sol. Slurry diumpankan ke pengering sembur dengan temperatur udara konstan 190oC, nisbah antara laju udara atomisasiterhadap laju alir umpan 0,75:1-1:1, laju alir udara panas 0,2-0,3 m3/min, dan laju umpan masuk 15-20 mL/min. Percobaan menghasilkan distribusi ukuran partikel sebesar 0,3752 µm hingga 161,1770 µm. Nilai analisis sudut diam 41,4498 sampai 48,9666, menunjukkan kriteria sifat aliran antara passable dan poor. Pengolahan data percobaan dengan metode ANOVA menunjukkan kecepatan udara panas masuk dan interaksi antara nisbah laju udara atomisasi terhadap laju alir umpan dengan kecepatan udara panas masuk berpengaruh secara signifikan terhadap rata-rata ukuran partikel dan rentang distribusi ukuran katalis FCC.